Salvianolate Protects Hepatocytes from Oxidative Stress by Attenuating Mitochondrial Injury - Zhao, Qiang (Evid Based Complement Alternat Med, 2016)
Salvianolate is widely used to treat angiocardiopathy in clinic in China, but its application in liver diseases remains unclear. Our study aims to investigate the effect of Salvianolate on rat hepatic injury by protecting hepatocyte mitochondria. To evaluate the effects of Salvianolate on injured hepatocytes, alpha mouse liver 12 (AML-12) cells were induced with hydrogen peroxide (H(2)O(2)) and treated with Salvianolate. Cell viability and MitoTracker Green for mitochondria and 5,5′,6,6′-tetrachloro-1,1′,3,3′-tetraethylbenzimidazole-carbocyanide iodine (JC-1) levels and cytochrome C (Cyto-C) expressions were detected in vitro. To identify the effect of Salvianolate on protecting against mitochondria injury, male Wistar rats were injected with carbon tetrachloride (CCl(4)) and treated with Salvianolate (40 mg·kg(−1)). Serum liver function, parameters for peroxidative damage, hematoxylin and eosin (H&E) staining, and transmission electron microscope (TEM) of hepatocyte mitochondria were assayed. Our results showed that Salvianolate effectively protected hepatocytes, increased mitochondria vitality, and decreased Cyto-C expressions in vitro. Besides, Salvianolate alleviated the liver function, attenuated the indicators of peroxidation, and relieved the mitochondria injury in vivo. In conclusion, Salvianolate is effective in protecting hepatocytes from injury in vitro and in vivo, and the mechanism might be related to its protective effect on hepatocyte mitochondria against oxidative stress.